Interleukin 6 and fetal fibronectin as a predictors of preterm delivery in symptomatic patients - Marija Hadži-Lega; Ana Daneva Markova; Milan Stefanovic; Mile Tanturovski (Association of Basic Medical Sciences of FBIH, 2014)
Preterm delivery is the leading cause of neonatal mortality and morbidity. The rate of preterm births has been estimated to be about 15 million, which accounts for 11.1% of all live births worldwide. The purpose of this study was to evaluate the cervico-vaginal (CVF) cytokine IL-6 and fetal fibronectin (fFN) status as predictors of preterm delivery in patients with symptoms of preterm labor. Patients with symptoms suggestive of preterm labor were recruited from September 2013 to March 2014. Vaginal swabs were taken for fetal fibronectin test (fFN) and CVF IL-6. Antibiotics, steroids and tocolytics were administered, where appropriate. The outcome was measured by the occurrence of preterm delivery within 14 days from the day of hospital admission. Cut-off value of 1305 pg/mL for the concentration of IL-6 in the CVF was the best predictor of preterm delivery, with the sensitivity of 69.4% and specificity of 68.2%. Patients with positive fFN test had the OR of 6.429 (95%CI 1.991-20.758) to deliver prematurely. The multivariate analysis of combined fFN and CVF IL-6 tests resulted in risk of 86.7% to deliver prematurely, if both tests were positive. The combination of both tests performed better than the individual tests and decreased the false positive rate, which in turn reduced the chances for inappropriate patient treatment, bringing down the costs.
Keywords: preterm labor; fFN; predictive value